DAMPAK RELATIONSHIP MARKETING, STORE ATMOSPHERE DAN LOKASI TERHADAP MINAT BELI PADA TOKO MOY STUFF - Onsardi Onsardi; Rola Dwita Fitri (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the impact of relationship marketing, Store Atmosphere and location on buying interest at the Moy Stuff store. This type of research is associative research, namely research that explains the influence between variables. The population in this study were all consumers in the Moy Stuff store. The sample of this study used the number of indicators used in the questionnaire with the assumption that n x 5 amounted to 115 people. The following conclusions can be drawn: 1).Relationship marketing has a positive effect on buying interest in Moy Stuff, thus the higher the relationship marketing, it will increase buying interest in Moy Stuff. 2). Store atmosphere has a positive effect on buying interest in Moy Stuff, thus the higher the store atmosphere, it will increase buying interest in Moy Stuff. 3). Location has a positive effect on buying interest in Moy Stuff, thus the higher the location, the more buying interest in Moy Stuff. 4).Relationship marketing, store atmosphere and location together show an influence on buying interest. Keywords: Relationship Marketing, Store Atmosphere and Location